The Relevance of Indigenous Knowledge Systems in Local Governance toward Environmental Management for Sustainable Development: A Case of Bulawayo City Council, Zimbabwe - Hari, Chiedza Angela (Quest Journal of Management and Social Sciences, 2020)
Background: Inspired by Bertalanffy (1954)’s Systems Theory, this study sought to establish the relevance of Indigenous Knowledge Systems (IKS) in local governance. Regardless of the overwhelming research on IKS, less attention has been put on its relevance to m.odern service delivery and seems to have lost its impact in influencing decision making. It was at the centre of this study,, therefore, to establish the relevance of IKS in local governance and establish the interconnectedness among local governance, IKS and environmental management for sustainable development. Predominantly, it focused on how IKS can be utilised as an integral system that contributes to the effective management of natural environment in urban cities, precisely Bulawayo Objective: The study strived towards contributing to the localisation of the Sustainable Development Goals within the Zimbabwean context in the best interest of the furtherance of sustainable cities for development with IKS at the centre of it all. Methods: Informed by the ontological interpretivist approach, this study adopted mixed methods of collecting data from 90 randomly selected residents of Bulawayo, three Environmental Management Agency officers and three Bulawayo City Council employees. Findings: One of the major findings was that IKS is silent in urban areas compared to the rural because of (although not limited to) a) lack of historical and sacred sites, b) ignorance of theexistence of IKS and c) adoption of technology. Referring to how IKS has been effectively utilised in the rural set up, this paper strongly believed that IKS as a system has an important role to play in this development discourse. Conclusions and Recommendations: Research should focus on the applicability of IKS in urban set up especial on its applicability to other environmental management aspects such as pollution and waste management. Implications: There must also be adequate transmission of information using proper channels for affirmation of IKS especially to the young generation and stakeholders should work together for sustainable management of the environment.